Предмет: Алгебра,
автор: mariakorol143
Задание 2.2
Спростіть вираз.
Приложения:
Ответы
Автор ответа:
0
сразу решаем
а+3 1 а*(а-1)
( ---------------- - ---------------- ) * --------------- =
(а-1)(а+1) а*(а+1) 3*(а+1)
а*(а+3) -1*(а-1) а*(а-1)
( ---------------------------- ) * ------------------- =
(а-1)(а+1)*а 3*(а+1)
а²+3а-а+1 а²+2а+1 (а+1)² 1
= --------------------- = ----------------- = --------------- = ---------
(а+1)*3*(а+1) (а+1)²*3 (а+1)²*3 3
а+3 1 а*(а-1)
( ---------------- - ---------------- ) * --------------- =
(а-1)(а+1) а*(а+1) 3*(а+1)
а*(а+3) -1*(а-1) а*(а-1)
( ---------------------------- ) * ------------------- =
(а-1)(а+1)*а 3*(а+1)
а²+3а-а+1 а²+2а+1 (а+1)² 1
= --------------------- = ----------------- = --------------- = ---------
(а+1)*3*(а+1) (а+1)²*3 (а+1)²*3 3
Похожие вопросы
Предмет: Математика,
автор: susannaasanova9
Предмет: Обществознание,
автор: Zig284838
Предмет: Литература,
автор: Mariskaqqqq
Предмет: Математика,
автор: 12Анюта1